Formation of students' social responsibility in a rapidly changing society - E. I. Antipova; R. A. Litvak (Вестник Северо-Кавказского федерального университета)
The article includes social and ideological presuppositions that actualize the necessity to form the social responsibility among the students in the conditions of the rapidly changing society. The study specifies the vectors to explore the process of the formation the social responsibility as a phenomenon of socio-cultural personal development where the values of the historically verified social experience and modern life-meaning guidelines are manifested. The aim of the article is to identify the level of formation of social responsibility among university students. The methods of research are assessment, synthesis and comparison of the material about the formation process of the social responsibility, a questionnaire, a survey according to the methodology by A. Makhnach, statistical processing of the data obtained during the survey. The results of the analysis demonstrate the formation of social responsibility among university students, the degree of understanding of social responsibility is determined. The results of the survey actualize the necessity to develop scientific and pedagogical ensuring the formation of social responsibility among the students in socio-cultural educational space.